2016
DOI: 10.1038/srep34728
|View full text |Cite
|
Sign up to set email alerts
|

Preserved implicit mentalizing in schizophrenia despite poor explicit performance: evidence from eye tracking

Abstract: Schizophrenia has been characterized by an impaired mentalizing. It has been suggested that distinguishing implicit from explicit processes is crucial in social cognition, and only the latter might be affected in schizophrenia. Two other questions remain open: (1) Is schizophrenia characterized by an hypo- or hyper attribution of intentions? (2) Is it characterized by a deficit in the attribution of intention or of contingency? To test these three questions, spontaneous mentalizing was tested in 29 individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 57 publications
0
10
0
1
Order By: Relevance
“…They used different paradigms. Except for one study (Roux et al, 2016b), all described different eye movements in patients with schizophrenia compared to controls (Roux et al, 2014(Roux et al, , 2015(Roux et al, , 2016aPatel et al, 2020). Three studies described reduced viewing time on the face (Roux et al, 2014(Roux et al, , 2016aPatel et al, 2020), one described that patients spent more time observing contextual cues, which also highlighted the importance of time, based on which patients' mentalizing is delayed (Roux et al, 2016a).…”
Section: Eye Movements Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…They used different paradigms. Except for one study (Roux et al, 2016b), all described different eye movements in patients with schizophrenia compared to controls (Roux et al, 2014(Roux et al, , 2015(Roux et al, , 2016aPatel et al, 2020). Three studies described reduced viewing time on the face (Roux et al, 2014(Roux et al, , 2016aPatel et al, 2020), one described that patients spent more time observing contextual cues, which also highlighted the importance of time, based on which patients' mentalizing is delayed (Roux et al, 2016a).…”
Section: Eye Movements Measurementsmentioning
confidence: 99%
“…Three (Roux et al, 2014(Roux et al, , 2016bPatel et al, 2020) studies measured the mean fixation duration which refers to the processing of information. Two studies found increased mean fixation duration in patients, which may indicate less saccades, shorter scanning paths (Roux et al, 2014(Roux et al, , 2016b.…”
Section: Fixation Durationmentioning
confidence: 99%
“…Relatively few studies focused on implicit and spontaneous ToM. Roux et al found (21) preserved implicit mental-state attribution measured by eye-tracking, whereas explicit performance was impaired, however, they also detected slowdown of social context processing during intention attribution with a similar paradigm (22). Other investigations-which used animated geometric forms stimuli-found deficient spontaneous ToM skills characterized with incorrect social inferences in schizophrenia (8,10,11,23).…”
Section: Introductionmentioning
confidence: 99%
“…Ils semblent avoir pour intention une mise à jour de la caractérisation des endophénotypes schizophréniques et surtout la manière dont sont menées les expériences avec l'ajout de ces notions. Nous retrouvons d'ailleurs ces notions de manière significative dans notre littérature dans des articles à partir de 2016 (54,96,200,201).…”
Section: )unclassified